International, multicenter analysis of endoscopic full-thickness resection of duodenal neuroendocrine tumors : endoscopy - Wannhoff, Andreas; Nabi, Zaheer; Moons, Leon M. G.; Haber, Gregory; Ge, Phillip S.; Dertmann, Tobias; Deprez, Pierre H.; Korcz, Wojciech; Bouvette, Christopher; Mueller, Julius; Tribonias, George; Grande, Giuseppe; et al. (The American journal of gastroenterology, 2025)
INTRODUCTION:  - Nonexposed endoscopic full-thickness resection (EFTR) using a dedicated full-thickness resection device can be used to perform en bloc resection of subepithelial lesions throughout the gastrointestinal tract. In this article, we aim to evaluate the safety and efficacy of EFTR for the management of duodenal neuroendocrine tumors (dNETs). - METHODS:  - This was an international multicenter retrospective study of device-assisted EFTR for dNET. Study outcomes included rates of technical success, R0 resection, and adverse events (AEs). - RESULTS:  - A total of 171 patients were included across 35 centers. Lesions had a median size of 10 mm and were in the duodenal bulb in 143 cases (83.6%). Technical success was achieved in 164 (95.9%) and R0 resection in 123 cases (71.9%). The R0 resection rate for lesions located in the proximal third of the bulb was 62.0% compared with 83.9% for more distal locations (P = 0.002). The R0 resection rate was not affected by lesion size or depth of invasion. On multivariable analysis, date of resection (2021 onward) and location distal to the proximal third of the duodenal bulb were independent predictors of R0 resection, but not case volume per participating center. Follow-up information was available for 114 patients (66.7%) and demonstrated 2 recurrences over a median follow-up of 10 months. Severe AEs occurred in 3 patients (1.8%). - DISCUSSION:  - EFTR of dNET showed high technical success and R0 resection rates and very low rate of severe AEs. It could become endoscopic treatment of choice for dNET, at least for lesions not within proximity of the pylorus. - - - - - Export
Gesehen am 20.01.2026